Change in pain status in children with cerebral palsy. (15th November 2016) - Christensen, Rhandi; MacIntosh, Alexander; Switzer, Lauren; Fehlings, Darcy
Abstract : Aim: To identify factors associated with a change in pain over time in children with cerebral palsy (CP). Method: Pain was assessed at two time‐points by physicians and caregiver‐rated Health Utilities Index 3 (HUI3) pain scores. Results: One hundred and forty‐eight children out of 179 approached from outpatient clinics (83% response; 104 males, 44 females mean age 8y 8mo, range 3y–16y) across all Gross Motor Function Classification System (GMFCS) levels were included. Fifty‐five percent had changes in caregiver‐reported HUI3 pain. A backward stepwise multiple linear regression retained HUI3 pain score at visit 1 and GMFCS level ( F [2, 144] =23.40, R 2 =0.35; p <0.001) as variables associated with a change in pain status (HUI3 pain at visit 1: β =0.61, p <0.001; GMFCS level: β =−0.17, p <0.015). The association between HUI3 pain at visit 1 and GMFCS level was significant ( β =−0.15, p <0.036). There was an association between pain etiology and pain trajectory ( F [3, 144] =5.39, p =0.002). Post‐hoc testing revealed musculoskeletal pain had the greatest improvements compared with the no pain group ( p =0.006). Interpretation: Children with CP with more severe initial pain and higher gross motor function have lower pain at follow‐up indicating an improvement in pain status over time. What this paper adds: Fifty‐five percent of children with cerebral palsy changed caregiver‐rated pain status over two time‐points. Higher initial caregiver‐rated pain was associated with positive changes in pain. Higher levels of gross motor function were associated with positive changes in pain. Musculoskeletal pain was associated with greater improvements in pain. This article is commented on by Jahnsen on pages345–346 of this issue.